A Meta-Summary of Qualitative Findings on the Lived Experience among Culturally Diverse Domestic Violence Survivors. (1st September 2013) - Childress, Saltanat
Abstract : This meta-summary study explores, extracts, and summarizes themes from related qualitative studies on the lived experiences and coping mechanisms among culturally diverse domestic violence survivors. Using Sandelowski and Barroso's meta-summary strategy, a systematic literature review of articles published between 1990 and 2010 was conducted using a qualitative approach. Of a total of 802 studies, nine met the study inclusion criteria. This meta-summary of nine studies confirms the recurring themes in primary qualitative studies in the literature that illustrate women's experiences of domestic violence. These themes include (a) the effects of violence, (b) the cyclical nature of violence, (c) normalizing and tolerating violence, (d) the strength and resilience of victims, (e) barriers to help-seeking, and (f) the role of substance use in domestic violence. The review shows key cross-cultural differences in women's perceptions of abuse and the causes and strategies for responding to abuse. The review also reveals the lack of studies on domestic violence among women from Central Asia and the former Soviet Union.